Applying Qualitative Data Derived from a Rapid Assessment and Response (RAR) Approach to Develop a Community‐based HIV Prevention Program for Adolescents in Thailand. (September 2015) - Watthayu, Nantiya; Wenzel, Jennifer; Panchareounworakul, Kobkul
Abstract : N/A: HIV education programs are needed to address risk‐taking behavior for adolescents. The purpose of our study was to use the World Health Organization's Rapid Assessment and Response (RAR) method to design a community‐based, cultural‐ and age‐appropriate HIV prevention program for adolescents in Bangkok, Thailand. Adolescent single‐gender‐specific focus groups ( n = 3; 28 participants) were used to gather reactions/ideas about program topics/approaches. An adult, mixed‐gender group was held to review information identified by adolescents. Sessions were audiotaped and transcribed verbatim. Themes regarding HIV content and the process of implementation emerged from a qualitative content analysis of the data. Community representatives recommended incorporation of HIV information and risk‐prevention skills. Information delivery suggestions included small group discussions, interactive games/role‐playing, program materials/terminology, and HIV‐infected program facilitators. Community members provided critical input toward an HIV prevention program tailored to meet adolescents' unique needs/interests. The RAR model provides opportunities to engage communities in developing health‐related interventions.